The Role of GITR/GITRL Interaction in Autoimmune Diseases - Tian, Jie; Zhang, Beibei; Rui, Ke; Wang, Shengjun (Frontiers in Immunology, 2020)
Glucocorticoid-induced TNFR-related protein (GITR) is a member of the TNFR superfamily which is expressed in various cells, including T cells, natural killer cells and some myeloid cells. GITR is activated by its ligand, GITRL, mainly expressed on antigen presenting cells and endothelial cells. It has been acknowledged that the engagement of GITR modulates the innate and adaptive immune responses. Accumulated evidence suggests GITR/GITRL system is involved in the pathogenesis of tumor, inflammation and autoimmune diseases. In this review, we describe the effects of GITR/GITRL activation on effector T cells, regulatory T cells (Tregs) and myeloid cells; summarize its role and the underlying mechanisms in modulating autoimmune diseases.